PENGARUH STRUKTUR ORGANISASI TERHADAP KEEFEKTIFAN ORGANISASI DI SEKRETARIAT DAERAH (SETDA) KABUPATEN TASIKMALAYA - Adi Kurnia (JURNAL ILMIAH ILMU ADMINISTRASI, 2020)
Regional Secretariat (Regional Secretariat) both institutionally and functionally occupies a strategic position as the center of organizational and management activities in the region. Personally, the employees are a group of individuals who possess specialists and competencies that are bound by the structure in carrying out such complex tasks and functions; The dynamics of organizational development and government management shows the level of development is increasingly oriented towards the use of information technology. The problem of this research starts from the effectiveness of the Regional Secretariat organization in carrying out its function as a staff organization. The results of data analysis, Organizational Structure has a correlation (r) of 0.842 to Organizational Effectiveness. The Effect of Organizational Structure on Organizational Effectiveness is 70.8%. F Test Results, simultaneously there is a positive and significant effect between Organizational Structure on Organizational Effectiveness in the Regional Secretariat of Tasikmalaya Regency. Partially, the Complexity Dimension (X1), Formalization Dimension (X2) and Centralization Dimension (X3) have a positive but not significant effect on Organizational Effectiveness (Y) in the Regional Secretariat of Tasikmalaya Regency. The conclusion of this study is that organizational structure simultaneously has a positive and significant influence on Organizational Effectiveness and Partially, Complexity X1, Formalization X2, Centralization X3 has a positive but not significant effect on Organizational Effectiveness in the Regional Secretariat of Tasikmalaya Regency